3-D High Frequency Ultrasound Imaging by Piezo-Driving a Single-Element Transducer - He, Liyuan (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2022)
Electronic scanning of two-dimensional (2-D) arrays and mechanical or freehand scanning of one-dimensional (1-D) arrays have been mostly utilized for conventional three-dimensional (3-D) ultrasound (US) imaging. However, the development of 2-D arrays and the hardware systems are complicated and expensive, while freehand systems with positioning sensors and mechanical systems are mostly bulky. This article represents a novel scanning strategy for achieving high-quality 3-D US imaging with a high-frequency single-element transducer. A 42-MHz US transducer with a compact structure was designed and fabricated, which was excited in the 2-D vibration by a tubular piezoelectric actuator. A dedicated imaging system was set up and both B-mode and 3-D US imaging of a custom wire phantom have been carried out to evaluate the performance of the proposed transducer. Compared to the results obtained with the motorized linear translation stage, the reconstructed images obtained by the proposed resonance scanning method are accurate, demonstrating the feasibility of 3-D US imaging with a vibrating single-element US transducer